Measuring Capital Services by Energy Use: An Empirical Comparative Study - Jürgen Bitzer; Erkan Gören (University of Oldenburg, Department of Economics, 2013)
From an engineering perspective, a capital good's service is energy conversion - e.g., the physical 'work' done by a machine - and can thus be measured directly by the energy consumed in production. We show important empirical advantages of our concept over traditional measures. The empirical application reveals that our concept avoids a number of conceptual problems of the latter. Furthermore, our measure is more sensitive to fluctuations in economic activity and therefore captures the utilization of the capital stock better. In a growth accounting exercise, this results in higher TFP growth rates, especially in times of global recession.
Keywords: E22; D24; O47; 330; capital service; utilization; energy consumption; total factor productivity; growth accounting; Kapital; Kapazitätsauslastung; Energiekonsum; Messung; Produktivität; Theorie